MODEL PEMBELAJARAN PEMAKNAAN PADA MATERI SISTEM ORGANISASI KEHIDUPAN UNTUK MENINGKATKAN HASIL BELAJAR DAN MENUMBUHKAN KARAKTER SISWA SMP - Dewi Markiah; Rudiana Agustini; Toeti Koestiari (Universitas Negeri Surabaya, 2017)
This study aims to describe the application of meaning learning model in life organizational system material on learning feasibility, student activities, student responses, student learning outcomes (knowledge, skills and attitudes), and development character of discipline and responsibility. Subjects of the research are seventh grade students of SMP 2 Tanah Grogot, Paser district of East Kalimantan academic year 2014/2015. This is Pre-Experimental One Group Pre-test-Post Test Design research. Methods of collecting data in this research are observation, testing, and questionnaires. Technique of data analysis is using descriptive quantitative analysis. Based on the data analysis of the research obtain some findings: a) developed learning materials are generally valid and well categorized, b) observation of study feasibility is well categorized, c) students activity during the learning is quite active, d) students response to all learning components are good and positive, e) students learning outcomes on knowledge has increased which can be seen from both individual learning outcomes, skill and attitude learning outcome after the teaching learning process are well done, f) based on the observation, discipline and responsibility character during the teaching learning process has increased well. It is concluded that the application of meaning learning models purport to improve learning outcomes, grow the discipline and responsibility character on seventh grade of junior high school students Penelitian ini bertujuan untuk mendeskripsikan pengaruh model pembelajaran pemaknaan pada materi sistem organisasi kehidupan terhadap peningkatan hasil belajar siswa. Parameter penelitian yang diamati adalah keterlaksanaan pembelajaran, aktivitas siswa, respon siswa, hasil belajar siswa (pengetahuan, keterampilan dan sikap) dan pengembangan karakter disiplin dan tanggung jawab. Subjek penelitian adalah siswa kelas VII SMPN 2 Tanah Grogot Kab. Paser Kalimantan Timur tahun ajaran 2014/2015. Jenis penelitian Pre-Experimental One-Group Pretest-Posttest Design. Metode pengumpulan data menggunakan observasi, tes, dan angket. Teknik analisis data menggunakan analisis deskriptif kuantitatif. Hasil penelitian diperoleh beberapa temuan a) perangkat pembelajaran yang dikembangkan secara umum valid dan berkategori baik, b) keterlaksanaan pembelajaran berkategori baik, c) aktivitas siswa selama proses pembelajaran cukup aktif, d) respon siswa terhadap seluruh komponen pembelajaran baik dan positif, e) hasil belajar siswa aspek pengetahuan terjadi peningkatan pada hasil belajar secara individual, hasil belajar aspek keterampilan dan hasil belajar aspek sikap setelah mengikuti pembelajaran seluruh siswa tuntas, f) pengamatan karakter disiplin dan tanggung jawab selama proses pembelajaran mengalami peningkatan dengan predikat baik. Simpulan hasil penelitian ini bahwa penerapan model pembelajaran pemaknaan dapat meningkatkan hasil belajar dan menumbuhkan karakter disiplin dan tanggung jawab siswa SMP kelas VII.